Intermittent versus continuous erlotinib with concomitant modified "XELOX" (q3W) in first‐line treatment of metastatic colorectal cancer: Correlation With Serum Amphiregulin and Transforming Growth Factor Alpha. Issue 23 (1st October 2013) - Ma, Brigette B. Y.; Chan, Stephen L.; Ho, Wing M.; Lau, Wilson; Mo, Frankie; Hui, Edwin P.; Chan, Charles; Poon, Annette; Dattatray, Rasalkar D.; Wong, S. C. Cesar; To, Ka F.; King, Ann D.; et al.
Abstract : BACKGROUND: This study evaluated the activity of 2 schedules of erlotinib in combination with chemotherapy, and the prognostic significance of serum amphiregulin (AREG) and transforming growth factor alpha (TGFa) in metastatic colorectal cancer. METHODS: A total of 60 untreated patients were randomized to a "continuous" (CON; erlotinib 100 mg daily) or an "intermittent" (INT; erlotinib 150 mg on alternate day on day 2 to 14, then 150 mg daily on days 15 to 21) schedule of erlotinib with a modified XELOX (capecitabine plus oxaliplatin) regimen. Serum levels of AREG and TGFa were determined serially. RESULTS: Baseline characteristics were similar between the 2 arms. Of the 58 patients evaluated for response, there was a nonsignificant trend toward a slightly higher overall response rate in the INT arm (66.7%) versus the CON arm (56.7%). At a median follow‐up of 2.8 years, the median overall survival was 18.8 months (95% confidence interval = 11.3‐22.9 months) and 20.7 months (95% confidence interval = 12.5‐31 months, P = .19) for the CON and INT arm, respectively. KRAS mutation did not predict drug response. The 2 arms did not differ significantly in toxicity. Baseline serum TGFa was an independent predictor of progression‐free survival, whereas a drop in serum TGFa and AREG levels following 3 to 4 cycles of treatment were associated with shorter progression‐free survival and overall survival, respectively. CONCLUSIONS: The intermittent erlotinib schedule was associated with a higher response rate, although this is not statistically significant. Serum TGFa and AREG levels have prognostic significance in erlotinib‐treated patients with colorectal cancer, and further studies are warranted. Cancer 2013 ;119:4145–4153. © 2013 American Cancer Society . Abstract : This phase 2 study is the first to evaluate the biological effect of different schedules of erlotinib in metastatic colorectal cancer. This study also demonstrates the prognostic utility of serum epidermal growth factor receptor ligands in erlotinib‐treated patients with colorectal cancer.